Ecological mechanism and diversity in rice based integrated farming system. (August 2018) - Nayak, P.K.; Nayak, A.K.; Panda, B.B.; Lal, B.; Gautam, P.; Poonam, A.; Shahid, M.; Tripathi, R.; Kumar, U.; Mohapatra, S.D.; Jambhulkar, N.N.
Highlights: Ecological diversity was studied in rice-fish-duck (RFD) integrated farming system. Biological diversity was more dynamic in RFD compared to conventional farming. WQI and SQI showed a good prediction about ecological aspects of RFD. RFD utilizes maximum ecological niches, which enhances farm sustainability. Abstract: The dynamic and transitional characteristics of rice field ecosystems provide an excellent environment for integration with compatible components such as fish and duck, which enhances the overall productivity through the effective nutrient recycling. The ecological mechanisms underlying the rice-fish-duck system sustainability have not been studied in detail especially on soil and water chemistry, dynamics of plankton, microbe and benthic populations and their community compositions. Therefore, the present study was undertaken to understand the ecological significance and diversities of organisms in the processes of maintenance of soil health, nutrient recycling and sustainable productivity in different rice-based integrated farming systems. In the integrated system such as rice-fish (RF), rice-duck (RD), and rice-fish-duck (RFD); the physico-chemical parameters of water (dissolved oxygen, nitrate, ammonia, total alkalinity, dissolved organic matter, and total suspended solid) and soil nutrient levels were significantly higher compared to conventional system due to the continuous addition of fecal matters, scooping and churning of soil by fish and ducks in the paddy field ecology. The aquatic biological diversity including planktons (phyto- and zooplankton), soil benthic fauna and microbial populations were dynamic in integrated rice-based system, provides an indication of enhanced soil fertility and production sustainability. The observed decreasing trends of plankton and soil benthic populations in integrated systems (RF, RD and RFD) indicated that fish and ducks fed these materials in rice ecology. Higher productivity and profitability in term of rice equivalent yields (REY) and the ratio of output value and cost of cultivation (OV/CC) were achieved in integrated farming system as compared to conventional rice farming (CRF). Thus, the present study reveals that adoption of rice-fish-duck integrated farming system enhances total farm production and income. Besides, the evaluation of different indicator indices viz., water quality index (WQI) and soil quality index (SQI) have shown a good prediction about ecological aspects of agro-ecosystems and will be helpful in farm management decisions making processes for improving farm productivity, profitability, and overcome any potential limiting factors in the rice-fish-duck integrated farming system. Finally, the present study concluded that rice-fish-duck integration utilizes maximum ecological niches and converted into potential production processes, which enhances farm production, farmer income and improved the soil health through the effective nutrient recycling in the rice ecologies.